Composição e diversidade de cigarrinhas (Hemiptera: Auchenorrhyncha) potencialmente vetoras de fitoplasma em coqueirais no Brasil - Silva, Flaviana Gonçalves da (2018)
The lethal yellowing disease (LY) is an absent quarantine disease that poses a serious threat to coconut cultivation, at imminent risk of entering Brazil. Haplaxius crudus (Hemiptera: Cixiidae) is the only known vector of the phytoplasmas that cause the disease, while other sap-sucking planthopper species with phloem-feeding habit may also be potential vectors of this phytopathogen. This study surveyed Auchenorrhyncha in coconut plantations in three states in the Northeastern region and in Santa Izabel do Pará in the North of Brazil, analyzed seasonal variations in the Auchenorrhyncha community of dwarf coconut accessions, and surveyed the Auchenorrhyncha community on coconut hybrids. The Auchenorrhyncha were surveyed in the wet and dry seasons of 2015 in the Northeast and in May 2016 in Pará. The seasonal variation of the Auchenorrhyncha community on six dwarf coconut accessions was analyzed from March 2016 to February 2017; and the survey of the Auchenorrhyncha on six coconut hybrids was carried out in the transition period between the dry and rainy seasons, in the rainy, and the dry season of 2016 in Itaporanga D’Ajuda, Sergipe. The Auchenorrhyncha were captured in the coconut canopy with yellow sticky traps. In the analysis, the captured insects were classified in seven and four Auchenorrhyncha families, respectively, in the Northeast and Pará. The planthopper H. crudus was only found in Santa Izabel do Pará, in the northern region, where it accounted for 87% of the captured individuals. In the community of Auchenorrhyncha on dwarf coconut palm trees, some of the most abundant species, such as Oecleus sp., Balclutha sp., Deltocephalinae sp.2, Deltocephalinae sp.3, Cenchreini sp., Omolicna nigripennis (Derbidae) and Cedusa sp., are potential phytoplasma vectors. Oecleus sp. was predominantly found on the accessions Cameroon Red Dwarf, Malayan Red Dwarf and Brazilian Red Dwarf Gramame, while Cenchreini sp. and Erechtia gibbosa (Membracidae) were dominant on Brazilian Yellow Dwarf Gramame, Malayan Yellow Dwarf and Brazilian Green Dwarf Jiqui. In the survey of coconut hybrids, 73% of the captured Auchenorrhyncha belonged to the species Oecleus sp. In the rainy season, composition of the Auchenorrhyncha communities on the hybrids Brazilian Green Dwarf Jiqui × Brazilian Tall - Praia Forte, Brazilian Green Dwarf Jiqui × Vanuatu Tall and Malayan Yellow Dwarf × West African Tall differed from those on Malayan Red Dwarf × Tagnanan Tall, Malayan Red Dwarf × Vanuatu Tall and Malayan Yellow Dwarf × Brazilian Tall-Praia Forte, and Curtara sp. and Oecleus sp., respectively, were the typical species of these two groups. This is the first report confirming the appearance of H. crudus and occurrence of other potential LY vectors in coconut plantations in Brazil, associated mainly with precipitation, followed by dwarf coconut and hybrid accessions. Knowledge about the occurrence of the vector species and other potential vectors in coconut plantations will contribute to the definition of contingency methods for coconut lethal yellowing contingency, in case this disease enters Brazil.